Essentials of oceanography - Garrison, Tom; Garrison, Tom (Australia, Brooks/Cole, 2009)
The fifth edition of ESSENTIALS OF OCEANOGRAPHY conveys Garrison's enthusiasm for oceanography to non-science students taking the introductory course. It is a streamlined version of his bestselling OCEANOGRAPHY text, but was created specifically to meet the needs of the shorter course. This text provides a basic understanding of the scientific questions, complexities, and uncertainties involved in ocean use, and the role and importance of oceans in nurturing and sustaining life on the planet.
Appendix 1-7, 389-406p.; Glossary 407-426p.; Index 427-434p.
Keywords: Oceanography; Geology